Structured decision making : a practical guide to environmental management choices - Gregory, Robin (Robin Scott) (Chichester, West Sussex ; Hoboken, N.J. : Wiley-Blackwell, 2012)
"This book is about the creative and messy process of making environmental management decisions. The approach we describe is called Structured Decision Making, a distinctly pragmatic label given to ways for helping individuals and groups think through tough multidimensional choices characterized by uncertain science, diverse stakeholders, and difficult tradeoffs. This is the everyday reality of environmental management, yet many important decisions currently are made on an ad hoc basis that lacks a solid value-based foundation, ignores key information, and results in selection of an inferior alternative. Making progress--in a way that is rigorous, inclusive, defensible, and transparent--requires combining analytical methods drawn from the decision sciences and applied ecology with deliberative insights from cognitive psychology, facilitation, and negotiation. We review key methods and discuss case-study examples based in our experiences in communities, boardrooms, and stakeholder meetings. Our goal is to lay out a compelling guide that will change how you think about making environmental decisions"--
"This book helps environmental managers frame natural resource management problems as decisions, so that difficult choices can be expressed clearly and in a way that is defensible and fits with common sense"--
-- Structuring environmental management choices -- Foundations of structured decision making -- Decision sketching -- Understanding objectives -- Identifying performance measures -- Incorporating uncertainty -- Creating alternatives -- Characterizing consequences -- Making trade-offs -- Learning -- Reality check : implementation -- Conclusion.
Includes bibliographical references and index.
Keywords: Environmental management -- Decision making